A diabetes peer support intervention: Patient experiences using the Mmogo-method® - Melanie A. Pienaar; Marianne Reid (AOSIS, 2021)
Background: Self-management is the backbone of diabetes care. For the patient with type 2 diabetes, this implies making decisions about a healthy diet, regular exercise and taking treatment appropriately. Some patients may experience barriers to the self-management of diabetes, such as lack of support. In this respect, peer support has been identified as a promising strategy in the self-management of diabetes. Aim: The study aimed to explore the experiences of adults with type 2 diabetes who took part in a diabetes peer support intervention in the Free State, South Africa. Such information may lead to the development of practical methods for diabetes self-management and control. Methods: Twelve purposively sampled Sesotho-speaking women (aged 51-84 years) participated in the Mmogo-method®, a visual-based narrative enquiry. Textual data from audio recordings of discussions, visual data from photographs of constructions and field notes were triangulated and analysed thematically. Results: Participants described the peer support intervention as very valuable. They regarded community health workers as an important source of support. Three themes emerged from the intervention: positive lifestyle changes, continuous support, and improved confidence and sense of connectedness. This was a significant finding reported in patients with diabetes, as it will contribute to successfully sustaining effective self-management behaviour. Conclusions: Peer support for patients with type 2 diabetes appeared to be a valued intervention, as participants related well to community health workers, who are ideally positioned in the healthcare system to provide the service.